HISTOLOGICAL AND HISTOMETRIC ALTERATIONS IN THE DIGESTIVE TRACT AND ACCESSORY GLANDS OF DUCK (Anasplatyrhynchos) WITH SEX AND PROGRESSIVE AGE - S. Qureshi; T. Faisal1and M. K. Saleemi; M. Z. Ali (Journal of Animal and Plant Sciences, 2017)
The current study was conducted to find morphological and histometrical variations in the digestive system and associated glands of duck (Anasplatyrhynchos) as regard to the sex and progressive age. A total of 30 apparently clinically healthy ducks of both sexes and three progressive age groups viz., immature (less than one year), adult (upto one year) and old (above one year) in equal number were used in this study. Digestive organs including tongue, esophagus, proventriculus, gizzard, small intestine, large intestine and associated glands like liver, pancreas and gall bladder were collected immediately after slaughtering the birds for histological studies. The sections of 5-7µm were cut and stained by haematoxylin and eosin stain. Histometrical analysis was done using automated computer software Image J®. The results of this study provide valuable information on the sex and age-related histological and histometrical variations in the digestive organs of ducks (Anasplatyrhynchos). Maturation in the organs of the digestive system is rapid in early days of life, that is from immature to adult age while it remains approximately fixed up to the old age.
Keywords: Histomorphometry; digestive organs; ducks; sex; age